The prevalence and risk factors of anxiety in multiple sclerosis: A systematic review and meta-analysis - Zhang, Xiaoyun; Song, Ying; Wei, Zhiqiang; Chen, Xiao; Zhuang, Xiaojia; Yi, Li (Frontiers in Neuroscience, 2023)
Background Patients with multiple sclerosis (MS) suffer from repetitive neurological deterioration, while anxiety may play a significant role in the disease’s progression. Objective To explore the prevalence of anxiety in MS and to investigate the risk factors related to anxiety in MS patients. Methods An analysis of four databases, PubMed, Web of Science, EMBASE, and Cochrane Library, has been conducted to determine the prevalence or risk factors for anxiety in MS published before May 2021. Results In total, 32 studies were found to be eligible. Anxiety prevalence was estimated to be 36% based on the pooled estimates [the 95% confidence interval (CI) = [0.30–0.42], I2 = 98.4%]. Significant risk factors for developing of anxiety were as follows: age at survey [the weighted mean difference (WMD) = 0.96, 95% CI = [0.86–1.06], I2 = 43.8%], female [the odd ratio (OR) = 1.78, 95% CI = [1.38–2.30], I2 = 0%], living together (OR 2.83, 95% CI = [1.74–4.59], I2 = 0%), past psychiatric history (OR 2.42, 95% CI = [1.56–3.75], I2 = 0%), depression (OR 7.89, 95% CI = [3.71–16.81], I2 = 0%), not taking MS medication (OR 2.33, 95% CI = [1.29–4.21], I2 = 77.8%), relapsing-remitting MS (RRMS) (OR 1.50, 95% CI = [0.94–2.37], I2 = 53.5%), and baseline Expanded Disability Status Scale (EDSS) (OR 0.84, 95% CI = [0.48–1.21], I2 = 62.2%). Conclusion An estimated 36% of people with MS suffer from anxiety. And anxiety rates in MS patients are significantly associated with age, gender, living together, prior psychiatric history, depression, drug compliance, RRMS, and baseline EDSS. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=287069, identifier CRD42021287069.